A qualitative approach to identify barriers to multi-professional teamwork among medical professors at Iranian teaching hospitals - Hakimeh Hazrati; Seyed Kamran Soltani Arabshahi; Shoaleh Bigdeli; Mozhgan Behshid; Zohreh Sohrabi (BMC, 2021)
Abstract Background In some cases of diseases, such as infectious, neurological and chronic ones prevention and treatment is complex. Therefore, a single medical specialty alone cannot effectively manage treatment of patients due to health care needs of them and complexities of treatment. Instead, a team composed of different healthcare disciplines with effective, continuous, and organized communication must follow up various aspects of patient care. In this regard, the present qualitative study aimed to shed light on the experiences of clinical teachers of multi-professional teamwork barriers within Iranian teaching hospitals. Methods In this qualitative research, the experiences of medical clinical teachers of multi-professional teamwork barriers within teaching hospitals were explained. Sampling was theoretical and the data were collected from experienced clinical teachers and medical students studying at several Universities of Medical Sciences through semi-structured interviews and observation, which were continued until data saturation. Fifteen clinical teachers and five medical students participated in the study. The interviews were analyzed using conventional content analysis. Results Three main categories were extracted. The first category was "enhancing the culture of interdisciplinary education" included "paving the way for an interdisciplinary culture", "enhancing teamwork culture", and "having a general view of medical sciences instead of specialization". The second category was "barriers of interdisciplinary education" included "influence of the dominant culture of specialization in society", "poor interdisciplinary education infrastructure", and "individualism as a value of society". And the third category was "consequences of specialization" included "medical sciences education under the shadow of specialization", "possibility to harming patients", and "distrust of society in the services provided by the 1st and 2nd level centers". Conclusion It seems that attitudinal barriers, teamwork difficulties, and the culture of individualism are evident in Iran; more, roles of the healthcare team and the status of each member is not clear. Designing interactive curriculum and arranging clinical settings to facilitate exchange of ideas among clinical teachers and students of different disciplines, is a step forward to achieving a common value concept, language, and common perception, and establishing cooperation and understanding among disciplines involved, which leads to further understanding of the professional responsibilities of other disciplines.